The Sculptor Qen (ii), His Two Wives, and the Men in his Family - Sweeney, Deborah (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
A detailed examination of the individuals mentioned in TT 4, the family tomb of the sculptor Qen (ii) and his two wives, Nefertari (vi) and Henutmehyt (iii), and on other family monuments, demonstrates that Nefertari (vi) was the senior of the two ladies of the house. The male relatives included in the representation of the funerary procession, and the ritual roles allotted to the children of each wife, are also key pieces of evidence leading to this conclusion.